Recycling potential for low voltage and high voltage high rupturing capacity fuse links. (December 2017) - Psomopoulos, Constantinos S.; Barkas, Dimitrios A.; Kaminaris, Stavros D.; Ioannidis, George C.; Karagiannopoulos, Panagiotis
Graphical abstract: Highlights: High breaking capacity fuse links are included in WEEE Directive, but no specific actions were taken systematically. Low voltage and high voltage high-rupturing-capacity fuse links recycling is possible. Recycling of fuse links will lead to significant materials recovery and metals. Recycling of fuse links will reduce industrial wastes and hazardous materials. Abstract: Low voltage and high voltage high-rupturing-capacity fuse links are used in LV and HV installations respectively, protecting mainly the LV and HV electricity distribution and transportation networks. The Waste Electrical and Electronic Equipment Directive (2002/96/EC) for "Waste of electrical and electronic equipment" is the main related legislation and as it concerns electrical and electronic equipment, it includes electric fuses. Although, the fuse links consist of recyclable materials, only small scale actions have been implemented for their recycling around Europe. This work presents the possibilities for material recovery from this specialized industrial waste for which there are only limited volume data. Furthermore, in order to present the huge possibilities and environmental benefits, it presents the potential for recycling of HRC fuses used by the Public Power Corporation of Greece, which is the major consumer for the country, but one of the smallest ones in Europe and globally, emphasizing in this way in the issue. According to the obtained results, fuse recycling could contribute to the effort for minimize the impacts on the environment through materials recovery and reduction of the wastes' volume disposed of in landfills.